Influence of Attitude towards Science to the Science Process Skills of Grade 10 Online Learners - Manguil, Carlo Jaime M; De Leon, Angeles M (Papanda Publisher, 2025)
The study investigates the influence of attitudes toward Science on the Science Process Skills (SPS) of Grade 10 online learners in Victoria Tarlac. Using descriptive and correlational research designs, data were collected from 120 respondents and analyzed through ANOVA and multiple linear regression. Findings revealed that self-concept positively predicts SPS, while anxiety negatively affects SPS. Additionally, significant differences were observed in SPS based on socio-demographic factors including sex, family income, and birth order. Female learners, students from higher-income families, and first-born children demonstrated better SPS performance. This study emphasizes the importance of fostering positive attitudes toward Science, such as self-concept, to enhance students’ SPS and reduce science-related anxiety. These results provide actionable insights for educators and policymakers aiming to improve science education and develop scientifically literate learners. By addressing these attitudinal and sociodemographic factors, the findings contribute to the broader goals of equipping students with essential skills for personal and societal development.